Efficient BiVO4 Photoanodes by Postsynthetic Treatment: Remarkable Improvements in Photoelectrochemical Performance from Facile Borate Modification. (8th November 2019) - Meng, Qijun; Zhang, Biaobiao; Fan, Lizhou; Liu, Haidong; Valvo, Mario; Edström, Kristina; Cuartero, Maria; de Marco, Roland; Crespo, Gaston A.; Sun, Licheng
Abstract: Water‐splitting photoanodes based on semiconductor materials typically require a dopant in the structure and co‐catalysts on the surface to overcome the problems of charge recombination and high catalytic barrier. Unlike these conventional strategies, a simple treatment is reported that involves soaking a sample of pristine BiVO4 in a borate buffer solution. This modifies the catalytic local environment of BiVO4 by the introduction of a borate moiety at the molecular level. The self‐anchored borate plays the role of a passivator in reducing the surface charge recombination as well as that of a ligand in modifying the catalytic site to facilitate faster water oxidation. The modified BiVO4 photoanode, without typical doping or catalyst modification, achieved a photocurrent density of 3.5 mA cm −2 at 1.23 V and a cathodically shifted onset potential of 250 mV. This work provides an extremely simple method to improve the intrinsic photoelectrochemical performance of BiVO4 photoanodes. Abstract : Eine BiVO4 ‐Photoanode wurde mit Borat auf molekularer Ebene (B‐BiVO4 ) durch ein Tauchverfahren modifiziert, was zu einem erhöhten Photostrom und einem geringeren Anfangspotential für die Wasseroxidation, vergleichbar mit der Beladung eines Cokatalysators, führte. Das Borat dient als Passivator zur Verringerung der Rekombination von Oberflächenladungen und als Ligand zur Modifikation der katalytischen Zentren.